Serious Games Development and Applications Third International Conference, SGDA 2012, Bremen, Germany, September 26-29, 2012, Proceedings - Ma, Minhua; Fradinho Oliveira, Manuel; Baalsrud Hauge, Jannicke; Duin, Heiko; Thoben, Klaus-Dieter (Image Processing, Computer Vision, Pattern Recognition, and Graphics, 2012)
This book constitutes the refereed proceedings of the 3rd International Conference on Serious Games Development and Applications, SGDA 2012, held in Bremen, Germany in September 2012. The 22 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers cover various topics on serious games including engineering, education, health care, military applications, game design, game study, game theories, virtual reality, 3D visualisation and medical applications of games technology.